2012
DOI: 10.1590/s0103-50532012000700016
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous spectrophotometric determination of Cu(II), Co(II) and Ni(II) using ratio spectra-continuous wavelet transformation in some food and environmental samples

Abstract: A razão entre o espectro contínuo e a transformada "wavelet" foi usada para a determinação simultânea de misturas ternárias de cobre, cobalto e níquel sem separação prévia. O método é baseado na reação de complexação destes cátions com 1-(2-piridilazo)-2-naftol (PAN) em meio micelar triton X-100, pH 8,0. Os resultados mostraram que Cu(II), Co(II) e Ni(II) foram determinados simultaneamente nos intervalos de concentração de 0,20-4,0, 0,20-4,0 e 0,50-7,0 mg L -1 , respectivamente. Foram selecionadas diferentes w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 30 publications
0
9
0
Order By: Relevance
“…So, the wavelets provide a new conception of a signal. WT is very effective for eliminating or reducing of baseline effect and noise of data, data compression, recognition and detection of latent transient information [24,28]. The combination of continuous wavelet transforms (CWT) and zero crossing technique has been adjusted for the simultaneous determination of different binary and ternary mixtures [29][30][31][32][33][34][35].…”
Section: Introductionmentioning
confidence: 99%
“…So, the wavelets provide a new conception of a signal. WT is very effective for eliminating or reducing of baseline effect and noise of data, data compression, recognition and detection of latent transient information [24,28]. The combination of continuous wavelet transforms (CWT) and zero crossing technique has been adjusted for the simultaneous determination of different binary and ternary mixtures [29][30][31][32][33][34][35].…”
Section: Introductionmentioning
confidence: 99%
“…Nowadays quantitative spectrophotometry has been greatly improved by the use of a variety of multivariate statistical methods, particularly partial least squares regression (PLS). It has been shown that PLS is a reasonable choice for the resolution of overlapping signals and quantitative analysis over a wide range of conditions [23][24][25][26] .…”
Section: Introductionmentioning
confidence: 99%
“…The process of cocrystallization is supramolecular self-assembly in nature, where all component molecules arrange themselves spontaneously via noncovalent interactions . Organic components are used for cocrystallization with 6-RsC2 is 1-(2-pyridylazo)-2 naphthol (PAN) (Scheme ), which is also an indicator used to determine the presence of specific metals, such as copper, zinc, and nickle. , Atwood et al. previously synthesized cocrystals from PAN and C -alkylpyrogallol­[4]­arenes (PgCs) with different C -alkyl chain lengths to study intermolecular interactions between components of cocrystals .…”
Section: Introductionmentioning
confidence: 99%
“…25 Organic components are used for cocrystallization with 6-RsC2 is 1-(2-pyridylazo)-2 naphthol (PAN) (Scheme 1), which is also an indicator used to determine the presence of specific metals, such as copper, zinc, and nickle. 26,27 Atwood et al previously synthesized cocrystals from PAN and C-alkylpyrogallol [4]arenes (PgCs) with different C-alkyl chain lengths to study intermolecular interactions between components of cocrystals. 28 Resorcin [4]arene and pyrogallol [4]arene have similar molecular structures, with only a variation of the number of hydroxyl groups on the upper rim of bowl shaped macrocycles.…”
Section: ■ Introductionmentioning
confidence: 99%